POLYAMOR: ANOTHER CONSENTED VIEW OF LOVING - Silva de Souza, Wagner (Health and Society, 2023)
Polyamory is a relationship practice where there are multiple loves, consent and simultaneous. It involves affection and not just sex between the parts that constitutes the polyamorist relationship. It’s a new nomenclature to conceptualize a contemporary relationship, challenging with the taboos of monogamous marriage of our society. The objective of this article is to accomplish a literature review that understand the reality of the polyamory, demystifying this theme and make an arrangement of how society sees such reality. It was made a bibliographic survey to understand the theme through an exploratory research, making the subject accessible for didactic purpose and information, as well as to abolish prejudice from an existing secular practice and that nowadays receive a new concept called polyamory. It’s perceptible, in the achieved results, a variable form that conceptualize the polyamory, but everyone comes together with the same idea and conclude that is a free practice, without jealousy, consented and where there are simultaneous and multiple loves, that the sexual practices are not necessarily presents concomitantly in all participants of the group.